P75NTR modulation counteracts alterations in neuronal and glial activity‐dependent profiles of gene co‐expression networks in tauopathy mice. (20th December 2022) - Latif‐Hernandez, Amira; Moran‐Losada, Patricia; Yang, Tao; III, Robert R. Butler; Tran, Kevin C; Liu, Harry; Massa, Stephen M.; Wyss‐Coray, Tony; Longo, Frank M.
Abstract: Background: P75 NTR is a key mediator in the regulation of neuronal plasticity, and modulation of its signaling prevents synaptic dysfunction in Tau.P301S mice, as measured by long‐term potentiation (LTP). Since LTP alters gene expression programs and results in transient post‐translational modifications at synapses, we asked whether tauopathy‐associated alterations in gene co‐expression, in response to stimulation, can be counteracted by p75 NTR modulation. Method: LM11A‐31 (C31), a small molecule p75 NTR modulator, was orally administered to Wildtype (WT) and Tau.P301S mice for 3 months, at a time when tau pathology was fully developed. RNA sequencing with cell‐type enrichment analysis was performed on unstimulated and stimulated hippocampal slices that underwent theta burst stimulation (TBS) to induce late‐phase LTP and generate activity‐dependent profiles of gene co‐expression networks, using weighted analysis with a soft‐threshold power of 18 to achieve scale‐free topology R 2 >0.8 and module size 25. Result: The most significantly expressed activity‐dependent transcriptional co‐expression modules related to synaptic function in WT mice, that were down‐regulated in Tau.P301S mice, showed an enrichment for genes in neurons and transcripts selectively expressed in CA1 pyramidal cells. The top significant gene pathways enriched in these modules were glutamatergic synapse, post‐synapse, pre‐synapse, post‐synaptic density, dendritic and neuron spine, with Cacna1h, Gabbr1, Kalrn, Shisa7, and Epha7. All of these were normalized to WT levels with C31 treatment. In addition, significantly up‐regulated co‐expression modules in Tau.P301S relative to WT mice associated with pathways such as complement binding, immune system process, myeloid leukocyte migration and neutrophil chemotaxis were enriched in genes found in microglia, such as Trem2, C1qa, C1qb, C1qc, Tyrobp. Notably, these expression profiles also reverted to WT levels with C31. Further, comparison of mouse and human modules demonstrated that those affected in treated mice have similar up‐ and down‐regulated patterns of expression as those found in human AD. Conclusion: Modulation of p75NTR with C31 normalized tauopathy‐related neuronal and glial transcriptional profiles. These transcriptional alterations are in part concordant with alterations found in human AD‐relevant gene co‐expression networks.